Profil Tingkat Stres Akademik Mahasiswa Fakultas Ilmu Pendidikan dalam Pembelajaran Daring selama Pandemi Covid-19 di Universitas Negeri Malang - Justice Afifah Ulul Albab; Ella Faridati Zen; Lutfi Fauzan; Justice Afifah Ulul Albab; Ella Faridati Zen (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2022)
Abstract: The stress experienced by students generally leads to academic stress. The phenomenon found in FIP UM, some students experienced barriers to learning online during the covid-19 pandemic. These obstacles have an impact on physical and psychological conditions, thus interfering with the optimal development of students. The purpose of this study was to determine the level of academic stress of S1 FIP UM students in online learning during the covid-19 pandemic. This research uses survey method with quantitative approach and descriptive design. The results of this study indicate that as many as 42 students are in the category of low academic stress with a percentage of 13.5 percent which means very few students have low levels of academic stress. A total of 184 students were in the category of moderate academic stress with a percentage of 59.2 percent, which means quite a number of students have moderate levels of academic stress. Furthermore, as many as 85 students are in the category of high academic stress with a percentage of 27.3 percent which means that few students have high levels of academic stress. Abstrak: Stres yang dialami mahasiswa umumnya mengarah ke stres akademik. Fenomena yang ditemukan di FIP UM, beberapa mahasiswa mengalami hambatan belajar secara daring selama pandemi covid-19. Hambatan tersebut berdampak pada kondisi fisik dan psikologis, sehingga menggangu tugas perkembangan mahasiswa yang optimal. Tujuan penelitian ini untuk mengetahui tingkat stres akademik mahasiswa S1 FIP UM dalam pembelajaran daring selama pandemi covid-19. Penelitian ini menggunakan metode survey dengan pendekatan kuantitatif dan rancangan deskriptif. Hasil penelitian ini menunjukkan sebanyak 42 mahasiswa berada di kategori stres akademik rendah dengan persentase sebesar 13,5 persen yang berarti sangat sedikit mahasiswa memiliki tingkat stres akademik rendah. Sebanyak 184 mahasiswa berada di kategori stres akademik sedang dengan persentase sebesar 59,2 persen yang berarti cukup banyak mahasiswa memiliki tingkat stres akademik sedang. Selanjutnya, sebanyak 85 mahasiswa berada di kategori stres akademik tinggi dengan persentase 27,3 persen yang berarti sedikit mahasiswa memiliki tingkat stres akademik tinggi.